STRATEGI PEMASARAN DALAM MENINGKATKAN PENJUALAN KAMAR DI THE TANIS BEACH RESORT LEMBONGAN PADA MASA PANDEMI COVID-19 - Vandini Putri Nurhabibah; Luh Komang Candra Dewi (Universitas Triatma Mulya, 2021)
This study aims to determine the competitive strategy applied by the company. This research was conducted at The Tanis Beach Resort Lembongan. The subjects in this study were department head managers and customers, totaling 20 people. This study was tested using SWOT analysis by identifying various internal and external factors of the company, namely the analysis of internal factors (strengths and weaknesses) and external factors (opportunities and threats) which were then formulated in the SWOT Diagram and SWOT Matrix. From the results of the analysis on the SWOT diagram it appears that the position of The Tanis Beach Resort Lembongan is located in Quadrant I which is described as a growth position, where internal factors total (3.02-3.56) so that the right strategy and results are needed to increase sales. rooms by strengthening market development, market penetration and product development. As well as facing several opportunities and having various driving forces to get these opportunities and it is recommended to carry out the SO, ST, WO, WT strategy. The strategy that can be applied by the company is to always issue promo packages and disseminate information to anticipate more attractive offers from competitors, such as collaborating with travel agents, updating information technology through digital marketing such as honeymoon package promos, fastboat ticket promos, and meeting promos. rooms.